Impedance Modeling and Stability Analysis for Cascade System of Three-Phase PWM Rectifier and LLC Resonant Converter - Rutian Wang; Yuyang Wu; Guoqing He; Ying Lv; Jiaxing Du; Yanhao Li (Energies, 2018)
In this paper; the impedance model of PWM rectifier and LLC resonant converter are deduced, and the stability analysis of cascade system is studied. The principle of three-phase PWM rectifier is introduced; and the small signal model in d-q coordinate system is deduced. The expression of dc side output impedance model for PWM rectifier is derived. The LLC resonant converter is operated in a fixed-frequency state, and the LLC resonant converter is modeled as a small signal model. On this basis, the input impedance model expression of the LLC resonant converter is derived. According to the impedance stability criterion, it can seen that the amplitude of input impedance is greater than the amplitude of output impedance in a certain frequency domain. In addition, the Nyquist curve is not around the point (−1,0), which can judge that the cascade system is stable. In simulation software, a cascade system simulation is built and corresponding simulation curves are obtained, which verifies the stability of the cascade system.